Validation of Support for Creation of License Drawings Using Application for openBIM-Based Automatic Generation of 2D Drawings - Inhan Kim; Yongha Lee; Choong-Hee Han; Gutaek Kim; Jungsik Choi (Applied Sciences, 2020)
In the preparation of drawings and documents required for a licensing process, the main problem is the duplication of work in creating design drawings and Building Information Modeling (BIM) models. To overcome this problem, BIM authoring tools provide a drawing generation function. However, it is difficult to use it in a construction project involving multiple actors using different authoring tools for each design actor. Owing to these problems, the drawing generation program, which is based the on the industry foundation classes (IFC) concept is not limited to the authoring tools used in the project, and it is intended to minimize duplication by outputting drawings in dwg and pdf formats. In this study, the IFC data structure required for generating drawings was analyzed and drawing elements on the basis of the shape and attribute information, certain drawing elements were output as 3D scenes in order to obtain detailed plan, elevation, cross-section, and structural drawings, which are required for an IFC-based licensing process. In addition, 2D drawings were generated through post-processing for obtaining drawing-level outputs. On the basis of BIM design guidelines, it was found that the information required in license drawings can be minimized, and the license licensing process can be based on a separate BIM technology. In other words, based on the licensing environment in Korea, the effectiveness of the automatic 2D drawing generation program was verified through a comparative analysis on the basis of the drawings and information required by assuming that a specific set of drawing elements were required in the existing licensing process and for BIM-based licensing. Furthermore, it was examined whether books required in the licensing process can be replaced by a parking lot plan that can be submitted through a BIM-technology-based legality review system.